Econometric Modelling of CGPA and its Associated Factors: A Study of Undergraduate Students of Riphah International University Malakand Campus - Khan, Zahid; Ismail, Muhammad; Hussain, Jawad; Khan, Muhammad Idrees (iRASD Journal of Economics, 2023)
This study is conducted to model the CGPA and its associated factors of undergraduate students of Riphah International University Malakand Campus Chakdara Dir lower, Pakistan. The stratified random sampling method is used to identify the students from population. The academic departments are considered as strata. One hundred and eight undergraduate students are selected for taking information from the University. Multiple Linear Regression (MLR) Model is used for modelling the CGPA and its associated factors. The MLR model shows that SSC obtained marks, parents’ education, parents’ support and attention in classes is significantly related with obtained CGPA of the students. In terms of policy recommendations, the results of this study present several policies for teachers, parents and administration. Both teachers and administration should focus on attention of students in class. Teachers should prepare interesting and informative lecture that students remain attentive in class. While administration should ensure standard class rooms consist of necessary facilities. Parents should support their children morally, financially and every aspect of life. Teacher and University administration should focus on those students who have illiterate parents. They should play role to guide the students more as their parents is illiterate. Finally, parents should ensure high marks of their children in previous classes that they can perform well in university. This study can be extended to other universities with large sample sizes. Other factors like teacher, environment and administration role can be consider for future study.